Establishment of an induced pluripotent cell line (ABCRIi001-A) from an elderly female for ageing research - Filipa Esteves; David Brito; Ana Teresa Rajado; Nádia Silva; Joana Apolónio; Vânia Palma Roberto; Raquel P. Andrade; Sofia Calado; Maria Leonor Faleiro; Carlos Matos; Nuno Marques; Ana Marreiros; et al. (Stem Cell Research)
Human induced pluripotent stem cells (hiPSCs) hold promises to model and understand human diseases, including those associated with ageing. Here, we describe ABCRIi001-A, a hiPSC line generated from peripheral blood mononuclear cells (PBMCs) of a 79-year-old female enrolled in a study for development of an ageing score (ALFA Score). PBMCs were reprogrammed using three Sendai virus-based reprogramming vectors (hKOS, hc-Myc, and hKlf4). ABCRIi001-A showed normal morphology and karyotype, viral clearance, absence of genomic aberrations, and their pluripotency was confirmed by expression of pluripotency-related markers and their ability to differentiate into the three germ layers. ABCRIi001-A is valuable for ageing-related studies.